Biallelic pathogenic variants in POLR3D alter tRNA transcription and cause a hypomyelinating leukodystrophy: A case report - Macintosh, Julia; Perrier, Stefanie; Pinard, Maxime; Tran, Luan T.; Guerrero, Kether; Prasad, Chitra; Prasad, Asuri N.; Pastinen, Tomi; Thiffault, Isabelle; Coulombe, Benoit; Bernard, Geneviève (Frontiers in Neurology, 2023)
RNA polymerase III-related leukodystrophy (POLR3-related leukodystrophy) is a rare, genetically determined hypomyelinating disease arising from biallelic pathogenic variants in genes encoding subunits of RNA polymerase III (Pol III). Here, we describe the first reported case of POLR3-related leukodystrophy caused by biallelic pathogenic variants in POLR3D, encoding the RPC4 subunit of Pol III. The individual, a female, demonstrated delays in walking and expressive and receptive language as a child and later cognitively plateaued. Additional neurological features included cerebellar signs (e.g., dysarthria, ataxia, and intention tremor) and dysphagia, while non-neurological features included hypodontia, hypogonadotropic hypogonadism, and dysmorphic facial features. Her MRI was notable for diffuse hypomyelination with myelin preservation of early myelinating structures, characteristic of POLR3-related leukodystrophy. Exome sequencing revealed the biallelic variants in POLR3D, a missense variant (c.541C > T, p.P181S) and an intronic splice site variant (c.656-6G > A, p.?). Functional studies of the patient’s fibroblasts demonstrated significantly decreased RNA-level expression of POLR3D, along with reduced expression of other Pol III subunit genes. Notably, Pol III transcription was also shown to be aberrant, with a significant decrease in 7SK RNA and several distinct tRNA genes analyzed. Affinity purification coupled to mass spectrometry of the POLR3D p.P181S variant showed normal assembly of Pol III subunits yet altered interaction of Pol III with the PAQosome chaperone complex, indicating the missense variant is likely to alter complex maturation. This work identifies biallelic pathogenic variants in POLR3D as a novel genetic cause of POLR3-related leukodystrophy, expanding the molecular spectrum associated with this disease, and proposes altered tRNA homeostasis as a factor in the underlying biology of this hypomyelinating disorder.